The African American roots of modernism : from Reconstruction to the Harlem Renaissance - Smethurst, James Edward (John Hope Franklin series in African American history and culture., 2011)
In identifying the Jim Crow period with the coming of modernity, Smethurst upsets the customary assessment of the Harlem Renaissance as the first nationally significant black arts movement, showing how artists reacted to Jim Crow with migration narratives, poetry about the black experience, and more.